A Case Series of Septicemia Due to Community-acquired Panton–Valentine Toxin Positive Methicillin-resistant Staphylococcus aureus in Children in Abidjan, Côte d'Ivoire - Richard Azagoh-Kouadio; Adjoua Sonia Djè; Sy Kadidia Savané; Claude Ghislain Tué-Bi; Toutou Ismael Koné; Sanemba Aya Fanny; Melissa Cardenat (Pediatric Infectious Disease)
Background: Staphylococcus aureus (SA) infections are one of the leading causes of morbidity and mortality worldwide. Community-acquired (CA) infections with Panton–Valentine leucocidin-positive methicillin-resistant Staphylococcus aureus (MRSA-PVL) have been increasingly reported around the world. The emergence of highly virulent resistant strains such as MRSA-PVL is associated with severe infections and poses a threat to child health in resource-limited settings, where their recognition and treatment are often delayed. Methods: This is a case series of 12 cases collected from 1st August 2020 to 31st August 2021, in a pediatric ward in Abidjan, Côte d'Ivoire. The inclusion criteria were sepsis with isolation of MRSA-PVL from blood cultures, no previous hospitalization, and no invasive medical or surgical procedures. We describe the epidemiological, clinical, and therapeutic features of this often-fatal infection. Results: Our patients' average age was 3.6 years, with a female-to-male sex ratio of 1:1. Skin lesions were present in 91.7% of patients. MRSA-PVL was isolated from all children in the blood. Antistaphylococcal antibiotic therapy was administered in all cases. A quarter of patients required surgical interventions. The hospital course was favorable for 9/12 patients (75%). All but one patient who developed pleural thickening (11.1%) recovered without sequelae (n = 8, 88.9%). A quarter of patients (n = 3) died due to septic shock. Conclusion: The emergence of strains of MRSA-PVL is a public health threat in emerging countries. Systematic and widespread epidemiological surveillance is needed to prevent its spread and inform appropriate clinical decision-making. Clinical significance: This case series highlights the need for a high index of suspicion for new antibiotic resistance patterns in emerging countries with limited microbiological diagnostic resources.